Ectopic production of beta‐hCG in anal cancer: A case report - Sierra Silverwood; Peter Kohler; Yelena Kier (Clinical Case Reports, 2024)
Key Clinical Message Beta‐hCG‐producing anal cancer, though rare, poses significant diagnostic challenges and may resist standard therapies. Recognizing the potential for hormone production in anal cancer is important, as it underscores the need for more specialized diagnostic techniques and tailored treatments. Abstract This case report describes the second reported case of ectopic production of beta‐hCG in anal cancer. A 53‐year‐old female presented with a new anal lesion. Biopsy showed a poorly differentiated squamous cell cancer (SCC) with undifferentiated sarcomatoid features, stage IIIA (cT2cN1cM0). Before starting concurrent chemotherapy and radiation, the patient had a positive urine pregnancy test. The beta‐human chorionic gonadotropin (beta‐hCG) production was attributed to the tumor, and upon completion of treatment, beta‐hCG normalized. Six weeks from treatment completion, recurrence was noted along with a positive beta‐hCG urine test. This case aims to highlight beta‐hCG as an ectopic hormone that can indicate the presence of squamous cell anal cancer and discuss the potential implications it may have on management.